The Process Approach in Forensic Activity as a Formalized Reflection of Its Stages and Algorithms - E. V. Chesnokova (Теория и практика судебной экспертизы)
The purpose of the study is to identify the matching and differing features of the concepts of “activity”, “algorithm”, “process”, “procedure”, “process approach” introduced into the theory of forensic examination by national and international standards of quality management systems and general requirements to testing and calibration labs for their subsequent adaptation to expert practice. The issue of the content of the term “process” in the theory of forensic examination, the basic principles and provisions of the process approach under the provisions of the standards: GOST R ISO IEC 17025- 2019 “General requirements for the competence of testing and calibration laboratories” and ISO 9001: 2015 “Quality management systems. Requirements” are addressed. The possibilities and advantages of introducing a process approach into forensic activity and forensic standard operating procedures are analyzed. The author concludes that forensic activity can be presented as a system of processes.